STUDI PENGARUH SIGNAGE TERHADAP ESTETIKA VISUAL KORIDOR JALAN AHMAD YANI MEDAN DITINJAU DARI ASPEK HARMONI DAN KONTRAS - Muharram, Ryan; Pakpahan, Raimundus; Napitupulu, Putri P. (Unika Santo Thomas, 2018)
Signage is one of the constituent elements of the city; there are so many types of signage, this study is limited to one type of signage only which is billboards. The diversity of existing billboards will be interesting when properly planned if the presence of billboards are not set properly and by its function than it is not impossible that the expected atmosphere can turn into an unpleasant atmosphere and damage the value of visual aesthetics. In the aesthetics there are harmony and contrast; as is a theory that supports the success of the design of public space regarding aesthetics is good to avoid the monotony and has a quality appeal. The research problem is how the billboards influence visual aesthetics on Ahmad Yani Medan road viewed from the aspect of harmony and contrast. Population in this research is billboards located along Jl. Ahmad Yani Medan. To complete the necessary data in this study, the researchers conducted data collection through observation and also the collection of related literature which became the main instrument in collecting primary data. This study is descriptive in which the data obtained in the field is collected and then analyzed, and the results described gradually in the form of writing. This study found that the influence of the existence of billboards along the road Ahmad Yani Medan has not fulfilled the aesthetic aspects in harmony and contrast.